ESTUDO SOBRE O IMPACTO DO SIAC SISTEMA DE AVALIAÇÃO DA CONFORMIDADE - NA IMPLEMENTAÇÃO DA NBR15.575:2013 EM EMPRESAS CONSTRUTORAS - Andery, Paulo; Barbosa, Patricia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present work aims presenting an exploratory study regarding the impact of the SIAC Quality Management System for Construction Companies, in its latest version, in the implementation of the NBR15.575:2013 in building construction companies. Case studies were carried out in six construction companies, and the research method is briefly outlined. The results point out that the quality management system was an important inductor of the implementation of NBR15.565:2013 requirements, mainly in the earlier phases of the design process. Some issues are outlined, highlighting the improvements on design review methods, better understanding of project technical constraints and risks and implementation of technological control plans at sites. Some features, such as design documentation and design scope definition need further improvements.